Highly Efficient Asymmetric Michael Addition Reaction of Malonates to α,β-Unsaturated Ketones Promoted by a Chiral Thiourea/PPY Dual-Catalyst System - Moritaka, Maya; Miyamae, Naomu; Nakano, Keiji; Ichikawa, Yoshiyasu; Kotsuki, Hiyoshizo (Synlett, 2012)
The enantioselective Michael addition reaction of malonates to α,β-unsaturated ketones is efficiently promoted by a combined dual-catalyst system composed of chiral thiourea and 4-pyrrolidinopyridine (PPY) in toluene. The expected Michael adducts with cyclic and acyclic enones are obtained in excellent yields and with excellent enantioselectivities.
Keywords: asymmetric Michael addition; malonates; α,β-unsaturated ketones; chiral thiourea; 4-pyrrolidinopyridine (PPY)